Trajectory of Kerala's development: C. Achutha Menon: Political biography - Reviewed by N. Shanmughom Pillai (Social Science in Perspective)
Pradeep Kumar. K.G., Keralavikasanathinte Nalvazhikal (Mal), C. Achutha Menon: Rashtriya jeevacharithram (Trajectory of Kerala's Development: C. Achutha Menon: Political Biography). Kollam: Sujilee Publication, 117p. Rs.280